Evaluation of the Characteristics of Transparent Solid Soap Fortified with Jeringau Rhizome Extract (Acorus calamus L) - Hairiyah, Nina; Nuryati, Nuryati; Fatimah, Fatimah; Meldayanoor, Meldayanoor; Amalia, Raden Rizki; Lestari, Ema; Linangsari, Titis; Salmah, Siti (Jurnal Teknologi Agro-Industri, 2025)
Transparent solid soap is a widely used cleansing product, yet formulation improvements are needed to enhance antibacterial activity while maintaining skin safety. This study aimed to investigate the effect of adding sweet flag rhizome extract (Acorus calamus L.) on the physicochemical properties, foam stability, pH, and antibacterial activity of transparent solid soap. Four soap formulations were prepared with varying extract concentrations: F0 (control, without extract), F1 (0.1 g), F2 (0.3 g), and F3 (0.5 g). The evaluated parameters included moisture content, total fatty acid content, free alkali, free fatty acids, foam stability, pH, skin irritation, and bacterial inhibition zone diameter. Data were statistically analyzed using one-way ANOVA and Duncan's Multiple Range Test (DMRT) at a 95% confidence level. The results showed that the addition of sweet flag extract significantly (p < 0.01) affected all tested parameters. The F3 formulation exhibited the highest antibacterial activity with an inhibition zone diameter of 15.5 mm but exceeded the SNI (Indonesian National Standard) limits for moisture content and pH, indicating a potential risk of skin irritation. However, skin irritation tests revealed that formulations containing the extract did not cause noticeable irritation in most panelists. It can be concluded that sweet flag rhizome extract has potential as an antibacterial agent in transparent solid soap formulations, although further optimization is required to reduce pH and free alkali levels to ensure product safety.